When Financial Support Crosses Boundaries: Educator-Mentor Voices on Family, Friendship, and Entrepreneurial Risk - Endi Rekarti; Sri Yusriani; Nur Mustofa Kamal; Bendaoud Nadif; Rifi Hamdani Sitohang; Muhammad Sidiq Idris Azzam (BCPR Research: Business Communication and Public Relations Journal, 2026)
Abstract: This study examines informal financial support within family, friendship, and entrepreneurial mentoring relationships from the voices of educators and mentors. The central issue is how support that begins as care may become burdensome when relational boundaries, written agreements, and business accountability are unclear. The study uses a qualitative approach through three waves of focus group discussions conducted from September 2025 to March 2026 with educators, mentors, and practitioners who had experience supporting learners or entrepreneurial communities. Thematic analysis produced five themes: financial support as a moral obligation, over-boundary care and hidden personal burden, trust without written agreement, vulnerability when close family or friends enter serious business, and the need for boundary governance before providing support. The article proposes the BOUNDARY framework as a practical guide to keep financial support humane, safe, and sustainable. It concludes that financial support may strengthen entrepreneurial intention and practice, but it must be accompanied by role clarity, written evidence, financial literacy, and protection of the supporter’s basic household stability.